1971
DOI: 10.1159/000220710
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of <i>Clostridium perfringens</i>Type A to Cephalosporin C Antibiotics <i>in vitro</i>

Abstract: Thirty strains of Cl. perfringens isolated from clinical material were found to be inhibited in vitro by 3 μg/ml or less of cephalothin and cephaloridine, 12 μg/ml or less of cephalexin and 6 μg/ml or less of cephaloglycin, as determined with the agar and microtiter broth dilution techniques. Cephaloridine appeared somewhat more active than cephalothin and cephaloglycin, while cephalexin appeared to be slightly less active than the former 3 cephalosporins, on a weight-for-weight basis. With few exceptions, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

1971
1971
1988
1988

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
1
5
0
2
Order By: Relevance
“…Any of the penicillins we tested should constitute effective therapy against C. perfringens. Our findings with cephalosporins agree with published results for cefamandole, cephalexin, cephaloridine, and cephalothin (16,17). Cefazolin, cefoxitin, and cephradine showed activity comparable to the other cephalosporins.…”
Section: Resultssupporting
confidence: 93%
“…Any of the penicillins we tested should constitute effective therapy against C. perfringens. Our findings with cephalosporins agree with published results for cefamandole, cephalexin, cephaloridine, and cephalothin (16,17). Cefazolin, cefoxitin, and cephradine showed activity comparable to the other cephalosporins.…”
Section: Resultssupporting
confidence: 93%
“…Pre-vious studies have shown that this organism is susceptible in vitro to a variety of commonly used antimicrobial agents (2,5,6,8,10,15,16). However, the constant, widespread use of antibiotics in the practice of both human and veterinary medicine necessarily entails the risk of the development of antibiotic resistance among some strains of C. perfringens.…”
mentioning
confidence: 99%
“…The Bauer-Kirby disk diffusion method was performed as before [1,6] em ploying Mueller-Hinton agar (Difco) with and without 5 %> sheep blood. The agar dilution as well as the microtiter broth dilution tests for clostridial isolates were performed according to the previously described techniques [6,8], Tube dilution tests for the 3 laboratory control strains were done as reported elsewhere [7], The MIC (minimal inhibitory concentration) was defined as the lowest concentration of gentamicin completely inhibiting growth as judged by visual inspection; the MBC (minimal bactericidal concentration) was the lowest concentration of anti biotic yielding no colonies from 3-mm loopful samples (roughly 0.03 ml) streaked to quarter sectors of sheep blood agar plates that were incubated anaerobically.…”
Section: Sensitivity Test Methodsmentioning
confidence: 99%
“…The same 30 clinical isolates of C. perfringens and the control strain of Sta phylococcus aureus that had been employed previously [6] were used in this study; additional control strains used were S. aureus 209 P and a strain of Escherichia coli, both of known antibiotic susceptibility.…”
Section: Strains Of C Perfringens Type Amentioning
confidence: 99%